2009
DOI: 10.1128/aac.01064-08
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Pharmacokinetic Study of Human Immunodeficiency Virus-Infected Patients Receiving Tenofovir Disoproxil Fumarate (TDF): Investigation of Systemic and Intracellular Interactions between TDF and Abacavir, Lamivudine, or Lopinavir-Ritonavir

Abstract: Previous work has demonstrated the existence of systemic interaction between tenofovir (TFV) disoproxil fumarate (TDF) and didanosine as well as between TDF and lopinavir-ritonavir (LPV/r). Here we investigated TDF interactions with the nucleoside reverse transcriptase inhibitors (NRTIs) lamivudine (3TC) and abacavir (ABC), comparing both the concentrations of nucleoside/nucleotide reverse transcriptase inhibitors in plasma and the intracellular concentrations of their triphosphate metabolites (NRTI-TP) for hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 42 publications
14
52
0
Order By: Relevance
“…Both doses were well tolerated, and no unexpected or serious adverse events related to the study medication were reported. The steady-state plasma 3TC and intracellular 3TC-TP pharmacokinetic parameters observed in the present study with 300 mg QD were comparable to that previously reported in healthy volunteers (2,3,28) and HIV-infected patients (2,9,14,17,18,21) receiving 3TC doses at 300 mg QD or 150 mg BID. However, there was marked intersubject variation in 3TC-TP concentrations, both here and in previous studies (the CV% invariably exceeded 50%), and differences between study centers, with some reporting slightly higher 3TC-TP concentrations (6 to 11 pmol/10 6 cells) in HIV-infected patients (13,21).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Both doses were well tolerated, and no unexpected or serious adverse events related to the study medication were reported. The steady-state plasma 3TC and intracellular 3TC-TP pharmacokinetic parameters observed in the present study with 300 mg QD were comparable to that previously reported in healthy volunteers (2,3,28) and HIV-infected patients (2,9,14,17,18,21) receiving 3TC doses at 300 mg QD or 150 mg BID. However, there was marked intersubject variation in 3TC-TP concentrations, both here and in previous studies (the CV% invariably exceeded 50%), and differences between study centers, with some reporting slightly higher 3TC-TP concentrations (6 to 11 pmol/10 6 cells) in HIV-infected patients (13,21).…”
Section: Discussionsupporting
confidence: 78%
“…The steady-state plasma 3TC and intracellular 3TC-TP pharmacokinetic parameters observed in the present study with 300 mg QD were comparable to that previously reported in healthy volunteers (2,3,28) and HIV-infected patients (2,9,14,17,18,21) receiving 3TC doses at 300 mg QD or 150 mg BID. However, there was marked intersubject variation in 3TC-TP concentrations, both here and in previous studies (the CV% invariably exceeded 50%), and differences between study centers, with some reporting slightly higher 3TC-TP concentrations (6 to 11 pmol/10 6 cells) in HIV-infected patients (13,21). Such variability in nucleoside triphosphate concentrations may be attributed to a number of interrelated factors that relate to the patient/host (immune status, cellular function, and genetic variation) intracellular pharmacokinetics (endogenous enzyme activity, competition with endogenous deoxynucleoside triphosphates, and concomitantly administered drugs) and differences in bioanalytical methods.…”
Section: Discussionsupporting
confidence: 78%
“…12 A potential biologic cause may be a pharmacokinetic interaction between lopinavir-ritonavir and tenofovir; decreased renal clearance of tenofovir and increased plasma and intracellular levels, particularly in women, have been reported with concomitant administration. [13][14][15] In the PROMISE trial, the lopinavir-ritonavir dose was increased during the third trimester because pharmacokinetic studies showed decreased lopinavir-ritonavir levels with standard doses in late pregnancy. 16,17 The ART regimens in the PROMISE trial were protease inhibitor-based because nevirapinebased ART was contraindicated in women with a CD4 count of more than 250 cells per cubic millimeter, and efavirenz, the other available nonnucleoside reverse-transcriptase inhibitor (NNRTI), was contraindicated in pregnancy at that time.…”
Section: Discussionmentioning
confidence: 99%
“…TFV, FTC, TFV-DP, FTC-TP, LPV, RTV, and RAL from extract samples were quantified using a Waters Acquity ultraperformance liquid chromatography (UPLC) system with a 2.1-by 100-mm, 1.7-m Acquity UPLC BEH RP18 shield column coupled to a Waters Xevo TQ-MS mass spectrometer operated in positive ion electrospray multiple-reaction-monitoring (MRM) mode. Two chromatographic conditions were used, one for FTC and TFV and another one for RTV, LPV, RAL, TFV-DP, and FTC-TP, both adapted from previously published methods (105,106).…”
Section: Methodsmentioning
confidence: 99%